Metformin and melatonin inhibit DMBA-induced mammary tumorigenesis in rats fed a high-fat diet. Issue 2 (February 2018) - Bojková, Bianka; Kajo, Karol; Kisková, Terézia; Kubatka, Peter; Žúbor, Pavol; Solár, Peter; Péč, Martin; Adamkov, Marián
Abstract : The data from in-vitro and in-vivo studies show that both peroral antidiabetic metformin (MF) and pineal hormone melatonin (MT) inhibit the growth of many cancers, including breast cancer. However, most in-vivo studies used standard-type diet with low fat content. Therefore, in this study, we evaluated the chemopreventive effect of MF and MT in an in-vivo model of breast cancer in rats on a high-fat diet (10% of total fat). Mammary carcinogenesis was induced by 7, 12-dimethylbenz[a]anthracene (DMBA) in female Sprague-Dawley rats. Chemoprevention with MF (administered in a diet, 0.2%) and MT (administered in tap water, 20 mg/l) was induced 20 days before the carcinogen administration through the termination of the experiment (14 weeks after carcinogen administration). Tumor growth parameters were analyzed together with histopathological examination and immunohistochemical detection of KI67 (proliferation marker), caspase-3, BAX, BCL-2 (apoptosis markers), and CD24 and CD44 (cancer stem cell markers) in mammary tumor samples. The combination of chemopreventive agents decreased tumor incidence by 29%. Cumulative tumor volume was lower in all groups treated with chemoprevention. Histopathology did not show significant changes in high-grade/low-grade tumor ratio. Immunohistochemistry showed increased expression of BAX in the combination group, and caspase-3 expression increased in both MT and combination groups. MT, and particularly the MF and MT combination, inhibited DMBA-induced mammary tumor growth in rats by apoptosis stimulation in cancer cells. Our results indicate that MT supplements in patients treated with MF may have a considerable effect on the incidence of breast cancer.